The Effect of Dehydroepiandrosterone (DHEA) Supplementation on IVF or ICSI: A Meta-Analysis of Randomized Controlled Trials - Xu, Lin; Hu, Chunxia; Liu, Qun; Li, Yaxuan (Geburtshilfe und Frauenheilkunde, 2019)
Introduction A systematic review and meta-analysis were conducted to evaluate the efficacy of dehydroepiandrosterone (DHEA) supplementation in patients with diminished ovarian reserve (DOR) and/or poor ovarian response (POR) who were undergoing in vitro fertilization or intracytoplasmic sperm injection (IVF/ICSI).Patients and Methods We searched the PubMed, EMBASE, Web of Science, and Cochrane Library electronic databases for literature published until July 2018. The analysis included randomized controlled trials (RCTs) of the effects of DHEA versus placebo on IVF or ICSI. Two independent reviewers extracted information from the reports and evaluated the quality of the studies. Overall, we identified nine prospective RCTs involving 833 patients.Results Compared to the controls, patients treated with DHEA exhibited increases in the number of retrieved oocytes (mean difference, 0.91; 95% confidence interval [CI], 0.23 – 1.59; p = 0.009), clinical pregnancy rate (relative risk [RR] = 1.27; 95% CI, 1.01 – 1.61; p = 0.04), and live birth rate (RR, 1.76; 95% CI, 1.17 – 2.63; p = 0.006). However, there was no intergroup difference in the miscarriage rate (RR, 0.37; 95% CI, 0.12 – 1.13; p = 0.08).Conclusion DHEA supplementation improved the outcomes of IVF/ICSI in women with DOR or POR.
Keywords: dehydroepiandrosterone (DHEA); diminished ovarian reserve (DOR); poor ovarian response (POR); in vitro fertilization (IVF); intracytoplasmic sperm injection (ICSI)